2021
DOI: 10.3390/met11040601
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Gas Pressure during Electron Beam Energy Deposition in the EBM Additive Manufacturing Process

Abstract: Electron beam melting (EBM) is a metal powder bed fusion additive manufacturing (AM) technology that facilitates the production of metal parts by selectively melting areas in layers of metal powder. The electron beam melting process is conducted in a vacuum chamber environment regulated with helium (He) at a pressure on the scale of 10−3 mbar. One of the disadvantages of vacuum environments is the effect of vapor pressure on volatile materials: indeed, elements in the pre-alloyed powder with high vapor pressur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 36 publications
0
10
0
Order By: Relevance
“…Additionally, a study on compositionally complex Al0.5CrMoNbTa0.5 high entropy alloy showed a decrease in the content of Al to 8.4 at% in build sample as compared to 12 at% in mechanically alloyed powder [23]. Some studies have recently proposed metalization control mechanisms, including vacuum [24] and process parameter control [25]. Damri et al [24] suggested increasing the pressure in the build chamber by one order of magnitude (from 10 −3 to 10 −2 mbar).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, a study on compositionally complex Al0.5CrMoNbTa0.5 high entropy alloy showed a decrease in the content of Al to 8.4 at% in build sample as compared to 12 at% in mechanically alloyed powder [23]. Some studies have recently proposed metalization control mechanisms, including vacuum [24] and process parameter control [25]. Damri et al [24] suggested increasing the pressure in the build chamber by one order of magnitude (from 10 −3 to 10 −2 mbar).…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have recently proposed metalization control mechanisms, including vacuum [24] and process parameter control [25]. Damri et al [24] suggested increasing the pressure in the build chamber by one order of magnitude (from 10 −3 to 10 −2 mbar). This did not significantly affect the energy efficiency of the electron beam but could help reduce the evaporation of elements.…”
Section: Introductionmentioning
confidence: 99%
“…Literature often carries the assumption that compositions are homogeneous in single-feedstock parts, as the powder remains the same throughout the build height [7,27]. However, during the initial and subsequent melting stages, melt pool interactions with the chamber environment include the evaporation and recondensation of elements, leading to local variations in composition [52][53][54][55][56] that are often neglected in the literature. In titaniumaluminum alloys specifically, including Ti-6Al-4V, high temperature processing, including various AM techniques such as EBM, is known to result in aluminum losses relative to the initial composition due to preferential vaporization during the processes [52,55,57].…”
Section: 2: Motivation and Problem Statementmentioning
confidence: 99%
“…However, during the initial and subsequent melting stages, melt pool interactions with the chamber environment include the evaporation and recondensation of elements, leading to local variations in composition [52][53][54][55][56] that are often neglected in the literature. The work presented…”
Section: Chapter 4 Influence Of Scan Strategy On Local Composition An...mentioning
confidence: 99%
See 1 more Smart Citation